The determination of the services of quantity surveyors - Abdul Lateef, Olanrewaju A.; Paul, Anavhe J. (2008)
The quantity surveying profession in Nigeria has made tremendous progress since the country gained independence in 1960. Quantity surveyors (QS) provide various kinds of services to a multitude of clients in the building industry. However, empirical researches focusing on the kind or category of services that they provide are somewhat inadequate and far between. This sometimes caused a rift among construction experts doubting what the QS actually do, vis-a-vis in providing clients with the necessary support and undertaking. Therefore, this paper seeks to determine the kind of services QS provide for their clients and benchmark it against established international standards. Distinguishing their scope of work will provide a clear direction for improvements and enable their special contribution to be better understood and appreciated. To achieve its objectives, the paper combined literature reviews and questionnaire survey. Henceforth, thirty six (36) general services expected of the QS in projects were identified and solicited among 200 respondents. The findings revealed that majoirty of the services were provided the quantity surveyors in nigeria. Howevere, a substantial percentage within the profession were not providing the required services to the clients. Therefore, the paper recommends for QS in Nigeria to strive for a more client-focused services in order to catch up with international standards and, along the way, improve service quality to meet the clients’ expectation.